Integrasi Nilai-Nilai Al-Farabi dan Ibnu Khaldun dalam Rekonseptualisasi Pendidikan Kewarganegaraan di Indonesia - Ade Nabila Hazanah; Syamzaimar Syamzaimar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study examines the integration of Al-Farabi’s and Ibn Khaldun’s values into the reconceptualization of Civic Education (PKn) in Indonesia. Civic Education has often been criticized for its normative orientation, which lacks relevance to the multicultural realities and democratic challenges of contemporary society. The objective of this research is to construct a conceptual framework that combines Al-Farabi’s emphasis on rationality, morality, and human perfection with Ibn Khaldun’s focus on social solidarity (asabiyyah) and adaptability to societal change. Using a qualitative descriptive approach with a library research design, this study analyzes classical and contemporary literature to identify the relevance of these contributions to PKn. The findings reveal that integrating Al-Farabi’s moral dimension and Ibn Khaldun’s social dimension enriches the ethical, spiritual, and civic aspects of PKn, while aligning with the foundational values of Pancasila. This integration offers a transformative model of PKn that not only develops cognitive competence but also nurtures moral integrity, social justice, and civic engagement. The implication is that PKn can serve as a holistic instrument for shaping citizens who are intellectually critical, ethically responsible, and socially cohesive. Nevertheless, the limitation of this study lies in its conceptual nature, as empirical testing has not yet been conducted, suggesting the need for further applied research to validate the proposed model.